The impact of direct benefits of control on the price informative value of voluntary information disclosure: An empirical study of the Iranian public listed companies - Zandi Pour Joopari, GholamReza; Shahabi, Alireza (2012)
The confiscations of properties left by the Royal family and the nationalization of large corporations and public companies following the Islamic Revolution in 1979 enlarged the State’s presence and activity in every sector of the economy, either through regular government agencies or public institutions such as charity foundations in Iran. The uncertainty over business dealings after the Revolution and no true financial picture of public companies listed on the TSE affected investors’ confidence level. These factors continued to stifle the Tehran Stock Exchange (TSE) until the Iranian second economic reform program was approved by the Parliament. According to the program, the government is committed to become a free market country with dispersed ownership and to sell out its block holdings in confiscated firms to private investors through the TSE.This paper seeks whether the voluntarily information disclosed by public companies listed on the TSE where the institutional block holders possess the Direct Benefit of Control (DBC) is useful and relevant information as a proxy for presenting true financial picture. We assumed that the relevant voluntary disclosure indicates more transparency so chose the annual reports of all public companies listed on the main board of TSE in 2009. Two types of indices were constructed, an index for the extent of voluntary disclosure (VD), and an index for the price informative voluntary disclosure (PID). The results show that the institutional block holders meet the needs of market for information by disclosing a lot of information (VD) but with less-relevant content in order to cover up their perks’ consumptions. The block holders would like to show the market is efficient with no information asymmetry however such transparency is not genuine. This paper may contribute to the literature where the presence of block holders shall increase the extent of voluntary disclosure (VD) while the transparency may decline.